Revisiting the Debate: Does Exercise Build Strong Bones in the Mature and Senescent Skeleton? - Hughes, Julie M.; Charkoudian, Nisha; Barnes, Jill N.; Morgan, Barbara J. (Frontiers in Physiology, 2016)
Traditional exercise programs seem to be less osteogenic in the mature and post-mature skeleton compared to the young skeleton, likely because of the decline in sensitivity of bone to mechanical loading that occurs with advancing age. Another factor contributing to the apparently diminished benefit of exercise in older adults is failure of widely used measurement techniques (i.e. DXA) to account for changes in 3-dimensional bone structure, which are important determinants of bone strength. Moreover, although hormonal contributors to bone loss in the elderly are well-recognized, the influence of age-related increases in sympathetic nervous system activity on bone is rarely considered. In this Perspective, we cite evidence from animal and human studies demonstrating anabolic effects of exercise on bone across the lifespan and we discuss theoretical considerations for designing exercise regimens to optimize bone health. We conclude with suggestions for future research that should help define the osteogenic potential of exercise in older individuals.